Analysis of the level of life in the Republic of Kazakhstan for 2003-2011 (Journal of Economic Research & Business Administration, 2015)
This article presents excerpts from the work of determining and comparing the standard of living of the population of Kazakhstan in 2003-2011. Research work carried out to the author's testing methodology for determining the standard of living for a time warp. In the research work of defining standards of living in the country was formed in the 2003, 2007 and 2011. In this paper, the definition 110 components levels and calculated on the basis of their 14 derivatives levels. Also, derived level of living in the synthesis level of generalizing. A comparative analysis of these components, derivatives, and generalizing the levels of different years. In the article due to the scale of research only bringing research to determine the consumer level, the level of property security, and the standard of living of the population in 2003-2011.
Keywords: living standard; index of living standard; generalizing index of living standard; derivative indexes of living standard; component indexes of living standard; level of consumption; level of property maintenance; level demographics